The training and development process for a multiple-Grand-Slam finalist in tennis - Haugen, T. A.; Ruud, C.; Bucher Sandbakk, S.; Sandbakk, Ø.; Tønnessen, E. (International Journal of Sports Physiology and Performance, 2024)
Purpose To investigate the training and development process of a multiple-Grand-Slam finalist.